2018
DOI: 10.1002/ajh.25306
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitor interruptions, discontinuations and switching in patients with chronic‐phase chronic myeloid leukemia in routine clinical practice: SIMPLICITY

Abstract: SIMPLICITY (NCT01244750) is an observational study exploring tyrosine kinase inhibitor (TKI) use and management patterns in patients with chronic phase‐chronic myeloid leukemia in the US and Europe in routine clinical practice. Herein we describe interruptions, discontinuations and switching of TKI therapy during the initial 2 years of treatment among 1121 patients prospectively enrolled between October 1, 2010 and March 7, 2017. Patient characteristics were broadly similar between the imatinib (n = 370), dasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
8
28
1
5
Order By: Relevance
“…Patterns of treatment interruptions, discontinuations, and switching in this analysis were consistent with those seen for the overall SIMPLICITY cohort after 2 years of follow‐up, which showed that a higher proportion of patients experienced these events in the first year of treatment than in the second 7 . These trends showing a decrease in these events in the second year extended to the third year, with the lowest proportion of European patients experiencing interruptions, discontinuations, and TKI switching in the third year of treatment.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Patterns of treatment interruptions, discontinuations, and switching in this analysis were consistent with those seen for the overall SIMPLICITY cohort after 2 years of follow‐up, which showed that a higher proportion of patients experienced these events in the first year of treatment than in the second 7 . These trends showing a decrease in these events in the second year extended to the third year, with the lowest proportion of European patients experiencing interruptions, discontinuations, and TKI switching in the third year of treatment.…”
Section: Discussionsupporting
confidence: 79%
“…These trends showing a decrease in these events in the second year extended to the third year, with the lowest proportion of European patients experiencing interruptions, discontinuations, and TKI switching in the third year of treatment. As previously observed for the overall SIMPLICITY population, 7 the key drivers for treatment changes in the European cohort were intolerances to TKIs and, to a lesser extent, resistance to TKIs. Although the proportions of patients with changes in treatment for intolerance declined year‐on‐year, the contribution of resistance to discontinuation of treatment increased after the first year of treatment.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Median age at diagnosis of CML is approximately 56 to 57 years in Western countries as estimated from the EUTOS and SIMPLICITY registries. 38 , 39 Patients older than 70 years make up more than 20%. In developing countries with younger populations median age is less than 50 years.…”
Section: Epidemiologymentioning
confidence: 99%